Workshop on Tectonic Evolution of Greenstone Belts : Houston, Texas, January 16-18, 1986 (Lunar and Planetary Institute, 1986)
A number of plate tectonic hypotheses have been proposed to explain the origin of Archean and Phanerozoic greenstone/ophiolite terranes. These hypotheses are explored in the abstracts. Compiled by, Publications Office, Lunar and Planetary Institute. PARTIAL CONTENTS: Komatiite Genesis in the Archean Mantle, with Implications for the Tectonics of Archean Greenstone Belts / D. Elthon -- The Yilgarn Craton Western Australia: A Tectonic Synthesis: I / R.E.P. Fripp -- Tectonics of Some Amazonian Greenstone Belts / A K. Gibbs -- Spatial Greenstone-Gneiss Relationships: Evidence from Mafic-Ultramafic Xenolith Distribution Patterns / A.Y. Glikson -- Dismembered Archean Ophiolite in the Southeastern Wind River Mountains, Wyoming-Remains of Archean Oceanic Crust / G.D. Harper -- Preliminary Report on the Geology and Gold Mineralization of the South Pass Granite-Greenstone Terrain, Wind River Mountains, Western Wyoming (USA) / W.D. Hausel -- The Kolar Schist Belt: A Possible Archean Suture Zone / G.N. Hanson, E.J. Krogstad, V. Rajamani, and S. Balakrishnan -- Evidence for Spreading in the Lower Kam Group of the Yellowknife Greenstone Belt: Implications for Archean Basin Evolution in the Slave Province / H. Helmstaedt and W.A. Padgham -- Archaean Wrench-Fault Tectonics in the Abitibi Greenstone Belt of Canada / C. Hubert and J.N. Ludden -- Transpression as the Main Deformational Event in an Archean Greenstone Belt, Northeastern Minnesota / P.J. Hudleston, D. Schultz-Ela, R.L. Bauer, and D.L. Southwick -- A Continuous Record of Tectonic Evolution from 3.5 Ga to 2.6 Ga in Swaziland and Northern Natal / D.R. Hunter, A.H. Wilson, J.A. Versfeld, A.R. Allen, R.G. Smith, D.W.W. Sleigh, P.B. Groenewald, G.M. Chutter, and V.A. Preston -- Is the Cameron River Greenstone Belt Allochthonous? / T.M. Kusky -- Sedimentological and Stratigraphic Evolution of the Southern Part of the Barberton Greenstone Belt: A Case of Changing Provenance and Stability / D.R. Lowe and G.R. Byerly -- Evidence for Structural Stacking and Repetition in ...